PATH ANALYTIC STUDY OF FACTORS AFFECTING ENTREPRENEURIAL INTENTION OF UNDERGRADUATE STUDENTS IN SOUTHWESTERN NIGERIA (2012)
The clamour for the inclusion of entrepreneurship in the curriculum of Nigerian universities has been on the increase. This growing interest may not be unconnected with the rapid rise in the rate of unemployment among school leavers in every facet of human endeavour. Studies on entrepreneurship in the developed countries have been extensive, but research work in Nigeria has not been adequate in investigating the psychosocial factors responsible for entrepreneurial intention. Therefore, this study investigated the causal effects of entrepreneurial self-efficacy, risk-taking propensity, creativity, locus of control, emotional intelligence, social capital, gender stereotype and field of study on entrepreneurial intention of undergraduate students in South-western, Nigeria.A survey research design of ex-post facto type was adopted. The population comprised undergraduate students attending six federal and two state universities in South-western, Nigeria. Two hundred and fifty questionnaires were sent to each of the universities used in the study. One thousand, seven hundred and seventy nine participants were sampled, using stratified random sampling technique. Eight instruments were used, namely, Entrepreneurial Self-Efficacy Scale (? = 0.62); Risk Style Scale (? = 0.78); Multidimensional Perceived Social Support Scale (? = 0.90); Rotter's Internal-External Locus of Control Scale (? =0.63); Emotional Intelligence Scale (? =0.90); Creative Personality Scale (? =0.77); Bem's Sex Role Inventory (? =0. 75), and Entrepreneurial Intention Questionnaire (? = 0.78). Six research questions were answered. Data were subjected to path analysis. A total of 24 direct and indirect significant pathways were identified. Out of these, five pathways were direct and these were: P93(emotional intelligence and entrepreneurial intention) (?=0.25), P94(locus of control and entrepreneurial intention) (? = -0.06), P95 (creativity and entrepreneurial intention) (? = 0.18), P96 (social capital and entrepreneurial intention) (? =-0.05), and P98(entrepreneurial self-efficacy and entrepreneurial intention) (? =0.12), while nineteen were indirect and these were: P42P84P98, P52P85P98, P62P76P87P98, P43P84P98, P63P86P98 and P53P75P87P98 among others. The total effects of the selected factors on entrepreneurial intention of the undergraduates indicated that 36.15% was direct, while 63.85% was indirect. Thus, the eight variables contributed a total of 20.4% to the total variance observed on the measure of entrepreneurial intention. Pattern of correlation in the observed data was consistent with the new model, with total difference of 0.047 and mean difference of 0.001.Consequently, the model is fit and tenable in explaining the causal effects of the independent variables on entrepreneurial intention. Emotional intelligence, creativity, entrepreneurial self-efficacy, locus of control and social capital have direct and indirect influence on entrepreneurial intention. It is, therefore recommended that training programmes relating to the stated factors be put in place to assist in fostering the entrepreneurial intention of students in the university campuses.